Molecular evidence that invasive adenocarcinoma can mimic prostatic intraepithelial neoplasia (PIN) and intraductal carcinoma through retrograde glandular colonization. Issue 1 (14th October 2015) - Haffner, Michael C; Weier, Christopher; Xu, Meng Meng; Vaghasia, Ajay; Gürel, Bora; Gümüşkaya, Berrak; Esopi, David M; Fedor, Helen; Tan, Hsueh‐Li; Kulac, Ibrahim; Hicks, Jessica; Isaacs, William B; et al.
Abstract: Prostate cancer often manifests as morphologically distinct tumour foci and is frequently found adjacent to presumed precursor lesions such as high‐grade prostatic intraepithelial neoplasia (HGPIN). While there is some evidence to suggest that these lesions can be related and exist on a pathological and morphological continuum, the precise clonal and temporal relationships between precursor lesions and invasive cancers within individual tumours remain undefined. Here, we used molecular genetic, cytogenetic, and histological analyses to delineate clonal, temporal, and spatial relationships between HGPIN and cancer lesions with distinct morphological and molecular features. First, while confirming the previous finding that a substantial fraction of HGPIN lesions associated with ERG‐positive cancers share rearrangements and overexpression of ERG, we found that a significant subset of such HGPIN glands exhibit only partial positivity for ERG. This suggests that such ERG‐positive HGPIN cells either rapidly invade to form adenocarcinoma or represent cancer cells that have partially invaded the ductal and acinar space in a retrograde manner. To clarify these possibilities, we used ERG expression status and TMPRSS2–ERG genomic breakpoints as markers of clonality, and PTEN deletion status to track temporal evolution of clonally related lesions. We confirmed that morphologically distinct HGPIN and nearby invasive cancer lesions are clonally related. Further, we found that a significant fraction of ERG‐positive, PTEN‐negative HGPIN and intraductal carcinoma (IDC‐P) lesions are most likely clonally derived from adjacent PTEN‐negative adenocarcinomas, indicating that such PTEN‐negative HGPIN and IDC‐P lesions arise from, rather than give rise to, the nearby invasive adenocarcinoma. These data suggest that invasive adenocarcinoma can morphologically mimic HGPIN through retrograde colonization of benign glands with cancer cells. Similar clonal relationships were also seen for intraductal carcinoma adjacent to invasive adenocarcinoma. These findings represent a potentially undervalued indicator of pre‐existing invasive prostate cancer and have significant implications for prostate cancer diagnosis and risk stratification. Copyright © 2015 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.